Revenue decentralization, central oversight and the political budget cycle: Evidence from Israel - Thushyanthan Baskaran; Sebastian Blesse; Adi Brender; Yaniv Reingewertz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This paper examines whether revenue decentralization and direct external financial supervision affect the incidence and strength of political budget cycles, using a panel of Israeli municipalities during the period 1999-2009. We find that high dependence on central government transfers - as reflected in a low share of locally raised revenues in the municipality's budget - exacerbates political budget cycles, while tight monitoring - exercised through central government appointment of external accountants to debt accumulating municipalities - eliminates them. These results suggest that political budget cycles can result from fiscal institutions that create soft budget constraints: that is, where incumbents and rational voters can expect that the costs of pre-election expansions will be partly covered later by the central government.
urn:nbn:de:bsz:180-madoc-394945
Keywords: D72; H72; H74; E62; 330; political budget cycles; soft budget constraint; local governments; decentralization